2014
DOI: 10.4161/gmic.29558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polysaccharopeptide fromTrametes Versicolorand amoxicillin on the gut microbiome of healthy volunteers

Abstract: The microbiomes of healthy individuals show substantial diversity but remain stable over time.The antibiotic amoxicillin alters the microbiome and recovery from this disruption can take several weeks. PSP from T. versicolor acts as a prebiotic to modulate human intestinal microbiome composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 46 publications
(72 reference statements)
3
45
1
Order By: Relevance
“…In recent studies using molecular techniques based on analysis of the prokaryotic 16S ribosomal RNA (16S rRNA) gene, loss of diversity and dramatic short‐term changes in several bacterial taxa have been a consistent finding after antibiotics exposure . Long‐term effects on microbial composition have also been reported in some studies, but with marked inter‐individual differences and even intra‐individual differences in the response to the same antibiotic ; thus, substantial relative changes in microbial abundances were seen several months after cessation of treatment with antibiotics in some studies , whereas other studies showed more modest effects on absolute bacterial numbers after treatment with antibiotics .…”
Section: Effects Of Antibiotics On the Human Gut Microbiotamentioning
confidence: 91%
“…In recent studies using molecular techniques based on analysis of the prokaryotic 16S ribosomal RNA (16S rRNA) gene, loss of diversity and dramatic short‐term changes in several bacterial taxa have been a consistent finding after antibiotics exposure . Long‐term effects on microbial composition have also been reported in some studies, but with marked inter‐individual differences and even intra‐individual differences in the response to the same antibiotic ; thus, substantial relative changes in microbial abundances were seen several months after cessation of treatment with antibiotics in some studies , whereas other studies showed more modest effects on absolute bacterial numbers after treatment with antibiotics .…”
Section: Effects Of Antibiotics On the Human Gut Microbiotamentioning
confidence: 91%
“…Dysbiosis is commonly characterized by a reduced diversity of the phyla Firmicutes and Bacteroidetes, and often accompanied by an overgrowth of the family Enterobacteriaceae [12,13,22,23,24,25]. This may become critical, as the healthy microbiota conveys colonization resistance towards invading pathogenic bacteria [26], and dysbiosis increases vulnerability for post-antibiotic expansion of enteropathogenic strains like Clostridium difficile [27] and antibiotic-resistant pathogens such as vancomycin-resistant Enterococcus [28].…”
Section: General Consequences Of Antibiotic Use On Gut Microbiota Commentioning
confidence: 99%
“…Although it is well known that antibiotics can disrupt gut microbial communities, 52,53 GePMI’s results indicate that most samples could still be correctly assigned to the original subjects after antibiotic treatment with no false positives. We noticed that some treated samples were no longer similar to the original samples.…”
Section: Resultsmentioning
confidence: 98%
“…23,33,65,66 A healthy individual’s microbial community is robust against external perturbations, demonstrated by its ability to maintain homeostasis and to recover from disease. 52,58,67 However, the exact process and path of its moving between a healthy state and a disease state remains a mystery, although we can distinguish the microbiota in an individual’s health state from that in the disease state. PMI may be applied to such cases to help us to understand this process and to design efficient intervention methods to cure the disease.…”
Section: Discussionmentioning
confidence: 99%